Preparation and Evaluation of Water-based Drilling Fluid HLR-1 Lubricant for Shale Gas Horizontal Wells - Chen Junbin, Ma Guangchang, Tao Huaizhi, Huang Jinjun, Lu Zeze (Forest Chemicals Review, 2022)
Shale gas horizontal wells often face problems such as wall instability, difficult borehole cleaning and high frictional torque during the drilling process. Among them, high frictional torque can cause a series of safety problems, such as start-up and down-drilling jam, buried drilling tool and buried rotary guide. To effectively solve this problem, this paper developed a water-based drilling fluid lubricant HLR-1 for shale gas horizontal wells using environmentally friendly modified vegetable oil, compound surfactant, extreme pressure anti-wear agent and coagulant as raw materials. Indoor evaluation showed that after adding the lubricant HLR-1 to the base mud, the apparent viscosity, density, mud cake adhesion coefficient and drilling fluid lubrication coefficient variation values of the base mud were in accordance with Q/SY 1088-2012 "Technical Specification of Liquid Lubricant for Drilling Fluid". The lubricant has good low temperature fluidity, high temperature resistance and salt resistance. It shows good compatibility in both dispersion drilling fluid system and polymer drilling fluid system. Compared with the commonly used lubricants RH-220, YKZJ-1, YRH-1 and YRH-1D, HLR-1 shows excellent lubrication performance in both base mud and field well mud, and the reduction rate of lubrication coefficient is 93.5% and 19.32%, respectively.